МАТЕМАТИЧНе МОДЕЛювання СТРУКТУРИ СТАЛЕВОГО ЗЛИВКА, ЩО ТВЕРДНЕ (Modern Problems of Metallurgy, 2020)
In this paper was considered existing models and methods that describe the crystallization of melts. A mathematical model for the crystallization of an ingot has been studied, taking into account shrinkage phenomena and the formation of a cone for deposition of finely dispersed crystals. A two-dimensional mathematical model of ingot crystallization is proposed using the method of splitting by physical factors.
Keywords: steel ingot, small divided crystals, solidification, motion of crystals, shrinkage shell, dendritic skeleton